«Մարտնչող անաստուածների միութիւնը»՝ կոմկուսի չկայացած նախագիծ - Յարութիւնեան, Աւագ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Союз воинствующих безбожников в Армении было основано в 1928 году, были изданы журнал и газета «Безбожник».Действуя в течение двух десятилетий при поддержке и покровительстве Коммунистической партии и советской государственной системы, союз насчитывал миллионы членов. Союз вел активную издательско-информационную деятельность, массовую пропаганду, но не добился намеченной заранее цели. Устранить фактор религиозного чувства из советской действительности не удалось. Советские граждане продолжали хранить веру в Бога, посещать церковь, отмечать религиозные обряды и праздники․ The “Union of Fighting Atheists” in Armenia was founded in 1928, which published a magazine and newspaper entitled “Atheist”. Operating for two decades with the support and patronage of the Communist Party and the Soviet state system, the Union had millions of members. The Union was active in publishing and information activities and mass propaganda, but it did not achieve its intended goal. It was not possible to eliminate the religiosity from the Soviet reality. Soviet citizens continued to keep their faith in God, attend churches, and celebrate religious rites and feasts.
Keywords: Պատմութիւն; Հայ եկեղեցւոյ պատմութիւն